Writing the review of literature: rasgulla as metaphor - Chattopadhyay, Nandita (Research and Humanities in Medical Education, 2014)
The author uses the metaphor of the Indian sweet, rasgulla, to unravel the details of how to conduct a literature search, and demonstrates thereby, how to structure a review of literature. The process also illustrates that a scientific temperament can be beneficial in any walk of life.